MiR322 mediates cardioprotection against ischemia/reperfusion injury via FBXW7/notch pathway. (August 2019) - Chen, Zixin; Su, Xuan; Shen, Yan; Jin, Yue; Luo, Tong; Kim, Il-man; Weintraub, Neal L.; Tang, Yaoliang
Abstract: Myocardial ischemia/reperfusion (MI/R) causes loss of cardiomyocytes via oxidative stress-induced cardiomyocyte apoptosis. miR322, orthologous to human miR-424, was identified as an ischemia-induced angiogenic miRNA, but its cellular source and function in the setting of acute MI/R remains largely unknown. Using LacZ-tagged miR322 cluster reporter mice, we observed that vascular endothelial cells are the major cellular source of the miR322 cluster in adult hearts. Moreover, miR322 levels were significantly reduced in the heart at 24 h after MI/R injury. Intramyocardial injection of mimic-miR322 significantly diminished cardiac apoptosis (as determined by expression levels of active caspase 3 by Western blot analysis and immunostaining for TUNEL) and reduced infarct size by about 40%, in association with reduced FBXW7 and increased active Notch 1 levels in the ischemic hearts. FBXW7, which is an ubiquitin ligase that is crucial for activated Notch1 turnover, was identified as a direct target of miR322 via FBXW7 3'UTR reporter assay. Co-injection of FBXW7 plasmid with mimic-miR322 in ischemic hearts abolished the effect of mimic-miR322 to reduce apoptosis and infarct size in MI/R hearts. These data identify FBXW7 as a direct target of miR322 and suggest that miR322 could have potential therapeutic application for cardioprotection against ischemia/reperfusion-induced injury.